Influence of zinc deficiency and supplementation on NK cell cytotoxicity. (September 2018) - Rolles, Benjamin; Maywald, Martina; Rink, Lothar
Graphical abstract: Zinc supplementation enhances NK cell activity by increasing perforin expression. Furthermore, zinc supplementation increased the interleukin (IL)-2 enhanced NK cell activity additively. In contrast, zinc deficiency reduced NK cell activity and dampened the IL-2 medicated enhancing effect on NK cells. Highlights: The trace element zinc has an enhancing effect on YTS cell killing activity. Zinc supplementation induces killing activity of primary NK cells from healthy donors. A rapid zinc influx after zinc deficiency boosts the NK cell cytotoxicity. Pre-incubation of malignant target cells with zinc facilitates apoptosis resistance. Abstract: Knowledge about the role of zinc on natural killer (NK) cell activity and function is limited and needs further instigation. Hence, in this study, the influence of interleukin (IL)-1, IL-2, zinc, and the zinc-chelator N, N, N′, N′-tetrakis(2-pyridylmethyl)ethane-1, 2-diamine (TPEN) on the human NK cell line (YTS cell line) and primary NK cells were examined. We mainly focused on NK cell killing activity by using the K562 cell line as target cells. We uncovered a significantly increased NK cell killing activity due to 1 h zinc pre-incubation and contact to zinc-rich medium in physiological concentrations. Moreover, co-stimulation of zinc and IL-2 provoked an additive increase in NK cell killing activity. In contrast, zinc deficiency induced by 1 h TPEN pre-incubation significantly decreased the killing activity of primary NK cells. Temporary elevated intracellular zinc levels in target cells act contrary to the destruction by NK cells.